Analisa Gambaran Post Mortem Makroskopis dan Mikroskopis Organ Jantung dan Ginjal pada Tikus Wistar Setelah Pemberian Warfarin LD50 dan LD 100 - Anggoro Adjar Mangestu; Gatot Suharto; Siti Amarwati (Jurnal Kedokteran Diponegoro, 2016)
Background : Its about 800.000 people die caused of suicide in a year. In 2012, suicide is the second most common cause of death in juvenile, range of age is 15-29 yo (WHO). One of common cause in suicide is using poison, and one of them is medical drugs. Warfarin is a substance which belong to medical drug as a human therapeutic agent but also can be use as a rodenticide. This study was aimed to analyze the effect of Warfarin administration in Wistar Rats organs especially brain and liver in a macroscopic and microscopic presentation.